2016
DOI: 10.1371/journal.pone.0161339
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude of the Association between Human Papillomavirus and Oral Lichen Planus: A Meta-Analysis

Abstract: BackgroundThe role of human papilloma virus (HPV) in oral lichen planus (OLP) is controversial.ObjectivesThe primary aim of the current study is to calculate the pooled risk estimates of HPV infection in OLP when compared with healthy controls.MethodsBibliographic searches were conducted in three electronic databases. Articles on the association between HPV and OLP were selected from case-control studies or cross-sectional studies, following predefined criteria. Pooled data were analyzed by calculating odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 33 publications
2
43
0
2
Order By: Relevance
“…25 In a recent meta-analysis which studied the immensity of the relation between HPV and OLP showed that OLP patients have significantly higher HPV prevalence (OR: 6.83; 95% CI: 4.15-11.27) than healthy controls. 26 Furthermore, it was observed that in the subgroup surveys, the association of HPV and OLP varied significantly according to the geographic region and population, among the 12 countries, in different continents. In the above-mentioned study, the ORs of HPV/OLP association were reported to range from 1.00 to 138.05.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…25 In a recent meta-analysis which studied the immensity of the relation between HPV and OLP showed that OLP patients have significantly higher HPV prevalence (OR: 6.83; 95% CI: 4.15-11.27) than healthy controls. 26 Furthermore, it was observed that in the subgroup surveys, the association of HPV and OLP varied significantly according to the geographic region and population, among the 12 countries, in different continents. In the above-mentioned study, the ORs of HPV/OLP association were reported to range from 1.00 to 138.05.…”
Section: Discussionmentioning
confidence: 97%
“…In the above-mentioned study, the ORs of HPV/OLP association were reported to range from 1.00 to 138.05. 26 The same meta-analysis investigated the association between HPV and the clinical forms of OLP (erosive-atrophic (EA) and non-EA) which was comparable and more intense in the EA OLP lesions (OR: 9.34) than in the non-EA OLP lesions (OR: 4.32). 26 In addition, in a previous study, the risk of progression to oral malignancy for non-EA OLP lesions was approximately 0.5%, whereas in the EA OLP, lesions increased at least to 3.5-4.00% during similar follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…98 Interestingly, an association between OLP and viral infections has also been reported. A recent meta-analysis 100 showed that patients with erosive OLP have a higher risk of HPV infection (HPV-16 and HPV-18), suggesting a potential causal role in OLP progression. Similarly, a possible association with HCV has also been reported.…”
Section: Oral Lichen Planusmentioning
confidence: 99%
“…Since the first report of the detection of HPV DNA in OLP biopsies, many groups have investigated the presence of HPV in oral tissues or exfoliated cells from patients with OLP and control subjects by polymerase chain reaction (PCR), immunohistochemistry, or in situ hybridization, but conflicting results have been reported. A recent meta‐analysis of 22 case–control studies concluded that patients with OLP have a significantly higher risk of HPV infection than healthy controls (35.09% vs 7.77%, odds ratio [OR] 6.83, 95% confidence interval [95% CI] 4.15‐11.27), with the variation depending on geography, clinical types of OLP, and HPV genotype …”
Section: Association With Viral Infectionmentioning
confidence: 99%